2014
DOI: 10.1007/s40618-014-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypovitaminosis D in patients with primary hyperparathyroidism

Abstract: High doses of oral cholecalciferol normalised vitamin D levels without worsening underlying hypercalcaemia in individuals with PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…Схеми можуть бути різні -по 20 000 МО 1 раз на тиждень ергокальциферолу або по 3000 МО щоденно, 1600 МО 1 раз на день холекальциферолу. Принципової різниці не виявлено між застосуванням ергокальциферолу та холекальциферолу щодо компен-сації недостатності вітаміну D. Необхідно зазначити, що навіть високі дози вітаміну D безпечно підвищують рівень сироваткового вітаміну D(25(ОН)D 3 і знижують рівень ПГ та зменшують резорбцію кісток у хворих на ПГПТ [6][7][8]. Призначення активних метаболітів віта-міну D недоцільне, оскільки вони не мають здатно-сті до кумулювання в печінці та жировій клітковині та мають короткий термін напіввиведення (4 доби), що для ергокальциферолу становить 14 днів.…”
Section: вступunclassified
“…Схеми можуть бути різні -по 20 000 МО 1 раз на тиждень ергокальциферолу або по 3000 МО щоденно, 1600 МО 1 раз на день холекальциферолу. Принципової різниці не виявлено між застосуванням ергокальциферолу та холекальциферолу щодо компен-сації недостатності вітаміну D. Необхідно зазначити, що навіть високі дози вітаміну D безпечно підвищують рівень сироваткового вітаміну D(25(ОН)D 3 і знижують рівень ПГ та зменшують резорбцію кісток у хворих на ПГПТ [6][7][8]. Призначення активних метаболітів віта-міну D недоцільне, оскільки вони не мають здатно-сті до кумулювання в печінці та жировій клітковині та мають короткий термін напіввиведення (4 доби), що для ергокальциферолу становить 14 днів.…”
Section: вступunclassified
“…Second, Rolighed et al [12] have recently demonstrated that daily supplementation with 2800 IU of vitamin D safely improves vitamin D status and decreases PTH. Finally, Rathi et al [13] in this issue of the Journal report on normalizing vitamin D nutritional status with significant reductions in serum PTH levels without any safety concerns.…”
mentioning
confidence: 99%
“…The conclusion of Rathi and co-workers [13] is that high oral doses of cholecalciferol normalise vitamin D levels without worsening underlying hypercalcemia in patients with primary hyperparathyroidism. Admittedly, further studies of longer duration are needed to better define the amount and modalities of refilling body stores with vitamin D. In the meantime, it seems prudent to suggest targeting vitamin D threshold (Endocrine Society, IOM), because this reduces the severity of the disease with no safety concerns.…”
mentioning
confidence: 99%
See 2 more Smart Citations